A Structure–Function Substrate of Memory for Spatial Configurations in Medial and Lateral Temporal Cortices. (27th February 2021) - Tavakol, Shahin; Li, Qiongling; Royer, Jessica; Vos de Wael, Reinder; Larivière, Sara; Lowe, Alex; Paquola, Casey; Jefferies, Elizabeth; Hartley, Tom; Bernasconi, Andrea; Bernasconi, Neda; Smallwood, Jonathan; et al.
Abstract: Prior research has shown a role of the medial temporal lobe, particularly the hippocampal–parahippocampal complex, in spatial cognition. Here, we developed a new paradigm, the conformational shift spatial task (CSST), which examines the ability to encode and retrieve spatial relations between unrelated items. This task is short, uses symbolic cues, incorporates two difficulty levels, and can be administered inside the scanner. A cohort of 48 healthy young adults underwent the CSST, together with a set of behavioral measures and multimodal magnetic resonance imaging (MRI). Inter-individual differences in CSST performance correlated with scores on an established spatial memory paradigm, but neither with episodic memory nor mnemonic discrimination, supporting specificity. Analyzing high-resolution structural MRI data, individuals with better spatial memory showed thicker medial and lateral temporal cortices. Functional relevance of these findings was supported by task-based functional MRI analysis in the same participants and ad hoc meta-analysis. Exploratory resting-state functional MRI analyses centered on clusters of morphological effects revealed additional modulation of intrinsic network integration, particularly between lateral and medial temporal structures. Our work presents a novel spatial memory paradigm and supports an integrated structure–function substrate in the human temporal lobe. Task paradigms are programmed in python and made open access.